Avaliação do agravamento de inundações na bacia hidrográfica do Alto Iguaçu e afluentes do Alto Ribeira, Paraná - Junior Ruiz Garcia (Confins)
The expansion of the urban net has been accompanied by soil waterproofing, contributing to the increased occurrence of flooding in these areas. However, the assessment of this phenomenon has not received due attention in the management of urban space, especially because there is not enough and adequate information. This study aims to assess the impact of changes in the land use in aggravation of foods in the Alto Iguaçu and Afluentes do Alto Ribeira Watershed, Paraná, Brazil. This watershed has a population of 3 million of people, with an important urban centre in Brazil. The proposal of change land use would respect the sustainable watershed scale, that represented by the information of its agricultural potential. The method used in this study was the Indicator of Aggravation Floods (IAF) for sub watershed. The results indicate that the chances in land use would reduce the probability of occurrence of flooding in the sub watersheds of the Alto Iguaçu and Afluentes do Alto Ribeira Watershed.